Gut Microbial Influences on the Mammalian Intestinal Stem Cell Niche - Peck, Bailey C. E. (Stem Cells Int, 2017)
The mammalian intestinal epithelial stem cell (IESC) niche is comprised of diverse epithelial, immune, and stromal cells, which together respond to environmental changes within the lumen and exert coordinated regulation of IESC behavior. There is growing appreciation for the role of the gut microbiota in modulating intestinal proliferation and differentiation, as well as other aspects of intestinal physiology. In this review, we evaluate the diverse roles of known niche cells in responding to gut microbiota and supporting IESCs. Furthermore, we discuss the potential mechanisms by which microbiota may exert their influence on niche cells and possibly on IESCs directly. Finally, we present an overview of the benefits and limitations of available tools to study niche-microbe interactions and provide our recommendations regarding their use and standardization. The study of host-microbe interactions in the gut is a rapidly growing field, and the IESC niche is at the forefront of host-microbe activity to control nutrient absorption, endocrine signaling, energy homeostasis, immune response, and systemic health.